(untitled) (LEARNing Landscapes, 2009)
Reading instruction in early primary grades tends to focus on segmenting words into sounds and there is little emphasis on explicitly teaching reading comprehension strategies.Through a kinesthetic approach, I attempted to make the invisible process of applying reading comprehension strategies visible. Students used a remote, similar to that of a TV, to play and pause their reading process.This enabled them to effectively use meaning-making strategies which took shape through signaling. Students would physically motion to themselves various signs which indicated the four reading comprehension strategies modeled in my think alouds (visualization, questioning, making predictions and making connections). The outcome was a highly motivated group of grade one students who could apply reading comprehension strategies and engage in discourse that reflected a higher level of understanding.